The Role of F-18 FDG PET/CT in Intrahepatic Cholangiocarcinoma - Lee, Yeongjoo; Yoo, Ie Ryung; Boo, Sun Ha; Kim, Hyoungwoo; Park, Hye Lim; Hyun O, Joo (Nuclear medicine and molecular imaging, 2017)
Purpose The aim of this study was to evaluate the diagnostic and prognostic role of metabolic parameters of FDG PET/CT in patients with intrahepatic cholangiocarcinoma (ICC). Methods From December 2008 to December 2013, 76 FDG PET/CT scans performed for initial staging of ICC in a single institution (57 male and 19 female; mean age 68 ± 9 years) were retrospectively reviewed. Patients with history of other known malignancy were excluded. Detection rates of regional lymph node and distant metastasis by FDG PET/CT were analyzed in comparison with conventional imaging modalities such as CT or MRI. Metabolic parameters including maximum, peak and mean standardized uptake values (SUVmax, SUVpeak, SUVmean), metabolic tumor volume (MTV), total lesion glycolysis (TLG), glucose corrected SUV (SUVgluc), and glucose corrected TLG (TLGgluc) were measured for the primary tumor. Cut-off values for the metabolic parameters were calculated by ROC curve analysis, and used to dichotomize the patient groups. The overall survival time (OS) was calculated and compared using the Cox proportional hazard regression analysis. Results The median duration of follow-up period was 5.4 months (interquartile range: 1.45∼15.45). FDG PET/CT showed higher sensitivity than conventional imaging modalities in detection of regional node involvement (74.5 % vs. 61.8 %, p = 0.013). In six patients, distant metastasis was identified only by FDG PET/CT. The mean SUVmax, SUVpeak, SUVmean, MTV, and TLG for the primary tumor were 8.2 ± 3.1, 6.8 ± 2.5, 4.0 ± 0.8, 192.7 ± 360.5 cm 3 , and 823.7 ± 1615.4, respectively. Patients with higher (≥7.3, HR: 4.280, p = 0.001), higher SUVpeak (≥6.5, HR: 2.333, p = 0.020), higher SUVmean (≥3.9, HR: 2.799, p = 0.004), higher SUVgluc (≥8.1, HR: 2.648, p = 0.012), and higher TLGgluc (≥431.6, HR: 2.186, p = 0.030) showed significantly shorter survival time. By multivariate study, operability was an independent prognostic factor for longer survival (HR: 4.113, p = 0.005). Conclusion FDG PET/CT is an important diagnostic imaging tool in the nodal staging and detection of distant metastasis in ICC patients. Metabolic parameters may have a significant role as prognostic factors in patients with ICC.